Systematic literature review: Trend analysis on the design of lightweight block cipher - Abdul Alif Zakaria; Azni Hazlizan Ab Halim; Farida Hazwani Mohd Ridzuan; Nur Hafiza Zakaria; Maslina Daud (Elsevier BV, 2024)
Indexed by WOS/Scopus/ERA